Analysis of the Potential and Effectiveness of Advertising Tax Revenue in Sumedang Regency - Putri Anisa Agustina; Apiatno; Lilis Kartika (Journal of Business, Accounting and Finance, 2021)
Sumedang Regency is one of the regions with a relatively low percentage of advertisement tax revenue compared to other sources of tax revenue. The potential for advertising tax revenue is proportional to the development of business activities that use billboards to introduce products produced by entrepreneurs to the public. This is based on this study aims to determine how the potential for advertisement tax and the effectiveness of advertisement tax revenue in Sumedang Regency. The research method uses a descriptive quantitative approach, the sample object of this research is advertisement tax which is selected purposively. Data collection techniques with documentation, observation, and interviews. Research data analysis using descriptive statistics. The results show that the potential value of the advertisement tax is greater than the realization of advertisement tax revenue, the average development of the potential advertisement tax per year is 2.5%, which is greater than the realization of its revenue of 1.1%. The development of the number of advertisements on average each year increased by 4.7%, and the highest development of the types of advertisements was the type of billboards (sticking) by 13.3%, while the development of the lowest types of advertisements was the types of billboards by 0.5%. Then based on the realization ratio and the advertisement tax target, the effectiveness of advertisement tax revenue is in the "effective" category with an average value of 100% effectiveness.